Sistem Akuntansi Dana Kas Kecil di PT Macan Sejahtera Cahaya - Siagian, Ika Romauli; Siringoringo, Magdalena Judika Br; Harefa, Meilinda Stefani (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
Petty cash funds are used to make it easier to manage small purchases or operational costs that often occur every day. The system used in the company is a fluctuating cash system. This research aims to determine the implementation of the petty cash fund accounting system at PT Macan Sejahtera Cahaya. The study used descriptive qualitative method. The data source used is primary data. The data collection method used was interviews and documentation. The data analysis method used in this research is qualitative data analysis. The research results showed that there were expenditures that exceeded the petty cash balance which resulted in the petty cash being underfunded. So, petty cash users use their personal money to carry out transactions when there is a shortage of petty cash funds. Therefore, the outhor recommends that companies use a fixed cash system, because the amount of petty cash funds will be more controlled and there will be no shortage of petty cash funds.